Work motivation : history, theory, research, and practice - Latham, Gary P. (SAGE, 2012)
'Work Motivation' draws on the author's experiences as a staff psychologist in, and a consultant to, organizations. It is written with a 'mentor voice' that is highly personal and rich in examples, including enduring influences of mentors on researchers in the field.- Resumé vydavatel